Estimating maximal heart rate with the `220-age` formula in adolescent female volleyball players: A preliminary study - Nikolaidis, P. T.; Padulo, J.; Chtourou, H.; Torres-Luque, G.; Afonso, J.; Heller, J. (Human Movement, 2014)
Purpose. Although maximal heart rate (HRmax) is used widely to assess exercise intensity in training, there are limited data with regards to the validity of age-based prediction equations of HRmax in volleyball players. Therefore, the aim of the present study was to compare the measured-HRmax of two prediction equations (Fox-HRmax = 220 - age and Tanaka-HRmax = 208 - 0.7 × age) in young female volleyball players. Methods. The study involved 47 volleyball players (age 13.39 ± 2.01 years, body mass 54.0 ± 10.8 kg, height 162.7 ± 10.2 cm) who performed a graded exercise field test (20 m shuttle run endurance test) to assess HRmax. Measured-HRmax values were compared with the Fox and Tanaka prediction equations. Results. The results showed that mean scores for HRmax significantly differed between measured and predicted values (p < 0.001, ?2 = 0.49). Post-hoc tests revealed that Fox-HRmax overestimated measured-HRmax (mean difference 5.7 bpm; 95% CI [3.0, 8.5]), whereas Tanaka-HRmax was similar to measured-HRmax (-2.2 bpm; 95% CI [-4.9, 0.4]). HRmax did not correlate with age (r = 0.16, p = 0.291). Conclusions. The results of this study failed to validate the widely used `220-age` formula in volleyball players. Coaches and fitness trainers should take into account that the overestimation of HRmax by the Fox equation might lead to prescribing exercise at a higher intensity than what is targeted. Therefore, the Tanaka equation appears to offer a more accurate prediction equation of HRmax than the Fox equation in young female volleyball players.